2022
DOI: 10.1002/rmv.2344
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 outcomes in paediatric cancer: A large scale pooled meta‐analysis of 984 cancer patients

Abstract: We aimed to study the outcomes of COVID‐19 in paediatric cancer patients. On 26 October 2021, we did a systematic search for relevant articles in seven electronic databases followed by manual search. We included cancer patients aged ≤18 years. Event rates and the 95% confidence interval (95%CI) were used to report the results. We included 21 papers after screening of 2759 records. The pooled rates of hospitalisation, intensive care unit (ICU) admission and mortality were 44% (95%CI: 30–59), 14% (95%CI: 9–21) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…A recent meta-analysis has shown that the severity and mortality of COVID-19 in this population is higher in low-middle income countries, suggesting that the inclusion of countries with different health resources may influence the analysis of the severity of COVID-19 (2,9).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis has shown that the severity and mortality of COVID-19 in this population is higher in low-middle income countries, suggesting that the inclusion of countries with different health resources may influence the analysis of the severity of COVID-19 (2,9).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] A recent meta-analysis has shown that the severity and mortality of COVID-19 in this population is higher in low middle-income countries, suggesting that the inclusion of countries with different health resources may influence the analysis of the severity of COVID-19. 2,9 The comparison of the morbidity and mortality of COVID-19…”
Section: Introductionmentioning
confidence: 99%
“…The current outbreak of COVID-19 caused an unheard-of global threat to the practical and safe care for children with cancer. Moreover, the late diagnosis of many childhood cancers were due to limited access to healthcare due to the pandemic and fear of infection which prevented parents from seeking early medical evaluation of symptoms in their child (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%